SYSTEMS, METHODS AND APPARATUS FOR PREVENTION OF INJURY - MARTINEAU, Paul (2023)
Systems, methods and apparatus are provided through which in some implementations, a system calculates an indication of cranial-concussion or sequelae from a cranial-concussion of a subject using skeletal tracking and calculating joint angles at different time points from the motion, posture, jumping/landing mechanics and/or balance of the subject in different movements.